Exploring the sustainability landscape in an academic institutions - Alhazemi, Abdulrahman A (International Journal of Management and Sustainability, 2025)
Academic institutions emphasize sustainability to achieve an equilibrium of institutional image, social effect, and environmental responsibility. Previous studies have left gaps in their understanding of how institutional policies, organizational culture, and leadership styles could affect AIs' sustainability outcomes. The present research investigates how these elements impact environmental sustainability, social responsibility, and institutional reputation through communication techniques, institutional resources, cooperation, and commitment acting as mediating variables. Data was collected from 512 academic and non-academic members across Saudi Arabia using a quantitative research method and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show transformational leadership, a strong sustainability culture, and well-organized institutional policies which greatly improve sustainability results. Furthermore, the perspectives of academic and non-academic staff about sustainability significantly influence green initiatives within AI. The present study adds to the body of knowledge by carefully examining the gaps in earlier studies, especially regarding the lack of attention provided to how institutional frameworks and leadership interact to promote sustainability in academic environments. The findings provide valuable insight for university officials trying to include sustainability on their campuses. AI can significantly promote sustainability at a more significant level of society by supporting sustainable leadership and creating policies that support social and environmental responsibility.